Analisis Batuan Andesit Sebagai Bahan Bangunan Di PT. Harmak Indonesia Desa Hargowilis, Kepanewonan Kokap, Kabupaten Kulon Progo, Daerah Istimewa Yogyakarta - Jannah, Salsabila Raudlotul; Novandri Kusuma Wardana,; R. Andy Erwin Wijaya, (ReTII, 2023)
Andesite rock is an igneous rock that has an important role in the construction of buildings, infrastructure and roads with various advantages. the use of andesite as a building material must pay attention to various factors, namely size, shape, strength, density, durability and so on and the quality of andesite rocks must also meet certain requirements set out in SNI 03-0394-1989. Therefore, a feasibility study or rock engineering is needed so that the level of feasibility of the rock as a building material can be determined. from the results of the compressive strength test on 4 samples and the average value of compressive strength in andesite rock was 634.43 kg/cmÂ², from the shear resistance test conducted on 2 samples the average value of shear resistance was 16.26%. This water absorption test was carried out on 2 samples of andesite rock aggregates which resulted in an average value of 0.737%. So it can be concluded that the andesitic igneous rock at pt. harmak indonesia is not feasible and does not meet the requirements and quality of natural stone for building materials in accordance with the indonesian national standard (sni 03-0394-1989). Keyword : Andesite, Building Materials.